Pemilihan Turbin Angin Skala Kecil Berdasarkan Analisis Potensi Energi Angin Menggunakan Windographer - Dwi Risdianto; Nurry Widya Hesty; Toha Zaky; Rudi Purwo Wijayanto; Agustina Putri Mayasari; Ario Witjakso (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Wind energy is a renewable resource with significant potential for generating electricity, particularly in small islands not connected to the State Electricity Company (Perusahaan Listrik Negara, PLN) grid. This study estimated the electrical energy production of small-scale wind turbines using Windographer software, based on an analysis of wind energy potential utilizing the Weibull distribution. The research focused on selecting small-scale wind turbines tailored to the wind energy potential and electricity needs of Miangas Island, North Sulawesi. The estimation of electrical energy production was conducted using the frequency distribution of wind speeds recorded hourly at a height of 50 m over the 2011–2020 period. The analysis encompasses average wind speed, wind direction distribution, Weibull distribution, average wind power density, and the annual estimation of electrical energy production. The results indicated that Miangas Island had an average annual wind speed of 5.5 m/s, with a wind speed frequency distribution of 15% and an average wind power density of 160.9 W/m². Simulations based on the analyzed wind potential demonstrated that small-scale wind turbines with capacities of 50 kW, 35 kW, and 10 kW could generate 98,434.49 kWh/year, 75,738.78 kWh/year, and 15,875.48 kWh/year, respectively. Considering the energy supply-demand balance, a 35-kW wind turbine is identified as the optimal choice to meet the annual electrical energy demand of Miangas Island, which is approximately 25,550 kWh.